2007
DOI: 10.1146/annurev.clinpsy.2.022305.095229
|View full text |Cite
|
Sign up to set email alerts
|

Dialectical Behavior Therapy for Borderline Personality Disorder

Abstract: Since the introduction of Linehan's treatment manuals in 1993, dialectical behavior therapy (DBT) has been widely disseminated throughout multiple therapeutic settings and applied to a variety of diagnoses. The enthusiasm with which it was embraced by clinicians early on led some to question whether DBT's popularity was outstripping its empirical foundation. Most of the specific concerns raised regarding DBT's early empirical base have been meaningfully addressed in subsequent randomized controlled trials. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
193
0
16

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 415 publications
(212 citation statements)
references
References 35 publications
3
193
0
16
Order By: Relevance
“…Some Authors in efficacy-studies observed that short-term psychotherapy (in particular dialectical behavioral psychotherapy) can improve identity disturbance in patients affected by BPD enhancing the patient's sense of self and coherence in their feelings and thoughts (Swann et al, 2003;Lynch et al, 2007;Rowpke et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Some Authors in efficacy-studies observed that short-term psychotherapy (in particular dialectical behavioral psychotherapy) can improve identity disturbance in patients affected by BPD enhancing the patient's sense of self and coherence in their feelings and thoughts (Swann et al, 2003;Lynch et al, 2007;Rowpke et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Sabe-se que os pacientes borderlines apresentam um déficit no aprendizado das emoções decorrentes do ambiente invalidante presente em sua infância (Lynch, Trost, Salsman & Linehan, 2007). Isso faz com que neguem as expressões emocionais dos sujeitos e interpretem suas próprias experiências emocionais equivocadamente (McMain, Korman & Dimeff, 2001).…”
Section: Empatiaunclassified
“…Lynch et al (2007) apontam que um dos critérios da TCD para o tratamento de pacientes borderline é a participação do terapeuta em grupo de supervisão clínica. Dessa forma, além de ter flexibilidade com o paciente, deve ser flexível consigo mesmo e reconhecer que necessita de auxílio.…”
Section: Flexibilidade E Versatilidadeunclassified
See 1 more Smart Citation
“…Its success in reducing suicidal and non-suicidal self-injurious behavior (NSSI), reducing hospitalizations, and retaining patients in therapy has made it a standard treatment modality for this population, and numerous randomized clinical trials support its effectiveness [4][5][6]. In addition to these stability and safety-related variables, DBT has also resulted in increases in quality of life measures such as depression, hopelessness, suicidal ideation, social adjustment, and anger [7].…”
Section: Life Problemsmentioning
confidence: 99%